Effect of Pericampylus glaucus on plasma glucose concentration and lipid profile in streptozotocin-induced diabetic rats (Bangladesh Journal of Pharmacology, 2016)
The purpose of this study was to evaluate the effects of Pericampylus glaucus extract on plasma glucose concentration and lipid profile in normal and streptozotocin-induced diabetic rats. The ethanolic extract were administered orally at three different doses (400, 600 and 800 mg/kg) and glibenclamide (20 mg/kg p.o.) for 21 days after 72 hours of streptozotocin injection. During the short- and long-term studies, the extract was found to possess significant (p